A Traceless Site‐Specific Conjugation on Native Antibodies Enables Efficient One‐Step Payload Assembly. Issue 36 (27th July 2022) - Zeng, Yue; Shi, Wei; Dong, Qian; Li, Wanzhen; Zhang, Jianxin; Ren, Xuelian; Tang, Caihong; Liu, Bo; Song, Yuanli; Wu, Yali; Diao, Xingxing; Zhou, Hu; et al.
Abstract: Direct chemical modification of native antibodies in a site‐specific manner remains a great challenge. Ligand‐directed conjugation can achieve the selective modification of antibodies, but usually requires multiple extra steps for ligand release and cargo assembly. Herein, we report a novel, traceless strategy to enable the facile and efficient one‐step synthesis of site‐specific antibody‐drug conjugates (ADCs) by harnessing a thioester‐based acyl transfer reagent. The designed reagent, consisting of an optimized Fc‐targeting ligand, a thioester bridge and a toxin payload, directly assembles the toxin precisely onto the K251 position of native IgGs and simultaneously self‐releases the affinity ligand in one step. With this method, we synthesized a series of K251‐linked ADCs from native Trastuzumab. These ADCs demonstrated excellent homogeneity, thermal stability, and both in vitro and in vivo anti‐tumor activity. This strategy is equally efficient for IgG1, IgG2, and IgG4 subtypes. Abstract : A traceless one‐step synthesis of site‐specific antibody‐drug conjugates (ADCs) has been established using a novel thioester‐based acyl transfer design with an optimized Fc‐binding ligand, which enables ligand self‐release during payload assembly. This strategy exhibits excellent compatibility with various toxins, linkers, and IgG subclasses, implying the potential for broad applications in ligand‐directed protein modifications.